2022
DOI: 10.1007/s10658-022-02614-7
|View full text |Cite
|
Sign up to set email alerts
|

Critical-point yield loss models based on incidence and severity of wheat head blast epidemics in the Brazilian Cerrado

Abstract: Wheat head blast (WHB), caused by the fungus Pyricularia oryzae Triticum pathotype, is one of the most damaging diseases of wheat. In Brazil, the disease has limited the expansion of wheat in the tropical regions of the Cerrado biome. In this study, wheat yield (Y) and visual estimates of WHB incidence (I) and severity (S) (assessed 25 to 30 days after flowering) were measured in a single location in the Cerrado (Minas Gerais state) where field experiments were conducted during seven sequential years (2013 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In the second source, field experiments were set up to examine the impact of wheat head blast on wheat yields at a single location (Patos de Minas, MG, Brazil) from 2013 to 2019. The latter experiments were originally planned to investigate the effect of planting date on disease intensity and their data were used and made available in a previous study on yield loss due to wheat head blast (Dos Santos et al 2022a). In addition, three Brazilian spring wheat cultivars, all susceptible to wheat head blast, namely BRS 264, BRS 404, and MGS Brilhante, were utilized.…”
Section: Disease Data and Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second source, field experiments were set up to examine the impact of wheat head blast on wheat yields at a single location (Patos de Minas, MG, Brazil) from 2013 to 2019. The latter experiments were originally planned to investigate the effect of planting date on disease intensity and their data were used and made available in a previous study on yield loss due to wheat head blast (Dos Santos et al 2022a). In addition, three Brazilian spring wheat cultivars, all susceptible to wheat head blast, namely BRS 264, BRS 404, and MGS Brilhante, were utilized.…”
Section: Disease Data and Variablesmentioning
confidence: 99%
“…Incidence variable was binarized as either outbreak when incidence was equal or greater than 20% incidence or non-outbreak otherwise. The 20% threshold was defined based on our previous yield loss studies (Dos Santos et al 2022a) and the median value of its distribution. Out of the 143 epidemics, 65 were classified as a non-outbreak and 78 were classified as outbreak (Table 1).…”
Section: Disease Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, leaf blast sporadically occurs in Brazilian wheat fields when warm and wet weather during the early season might favor infection and inoculum build-up on young leaves (Cruz et al 2015). The first detailed report of yield losses due to wheat blast was estimated at around 27% in Brazil (Goulart et al 1990), but greater losses, nearing 100%, have also been reported (Coelho et al 2016;Dianese et al 2021;Santos et al 2022;Goulart and Paiva, 2000;Trindade et al 2006). In the first major epidemics in Bangladesh, in 2016, the disease caused losses in more than 15,000 ha, which resulted in complete destruction of some affected fields (Islam et al 2016;Malaker et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In such conditions, and if control measures (e.g. fungicide sprays) are not utilized, the disease can severely reduce crop yield by more than 80% (Coelho et al, 2016;Dos Santos et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%